Tinjauan Geologis Potensi Bencana Tanah Longsor Pada Ruas Jalan Sungguminasa Malino Kabupaten Gowa Sulawesi Selatan (Jurnal Geomine, 2021)
The role of the Sungguminasa – Malino Road in the movement of road users is very important in supporting the economy of Gowa Regency. First, Malino is one of the tourist destinations in Southern South Sulawesi. Second, this road segment is a road segment used to transport construction materials such as sand, gravel and river stone for infrastructure development in Sungguminasa City and Makassar City, the Sungguminasa-Malino road section is one of the roads made through bumpy topography to steep hills, For this reason, this research is important. Objective Of The Research is to analyze the potential for landslides on the Sungguminasa-Malino road and determine the types of landslides and their impacts., aspects observed in this study, namely the geometry of the slopes using a geological compass, the type of lithology determined megascopically using a loupe (magnification glass), and the degree of weathering of rocks was determined megascopically by observing and feeling the rocks. Research Results show that the slope is slightly steep to moderately steep locally and the rocks that make up the slope are fine tuff to coarse tuff that has undergone high weathering to complete weathering and in some areas has become residual soil. Conclusion, with the conditions as mentioned above, the research area has the potential to experience landslides. On land with steep to very steep slopes, there is the potential for landslides of the type of debris slide (at locations-2,3,4,5 and 6) and at location-1 in Bujjulu-Bilibili Village, the road body has subsidence. This information is very important for relevant agencies because by knowing the potential for landslides early, mitigation can also be done earlier.